Hormonal Responses to Exercise - Chaudhary, Sarika; Shenoy, Shweta (Highlights on Medicine and Medical Research Vol. 13, 2021)
This chapter deals with stress hormones which are released into the blood in varying amounts and elicits a typical physiological response to different types and modes of exercises. The response of all the hormones to exercise is influenced by intensity, duration, type of exercise, gender and age. The effects are also variable on trained and non trained athletes. As the hormones are secreted in various pulses throughout the day in a circadian pattern, so the effects of diurnal variation have also been explained. Other than exercise, there are varieties of stimuli such as hypoglycemia, caffeine, hypoxia, glucagon, and hypercapnia which can greatly stimulate the response of hormones. The chapter has covered a wide range of literature on growth hormone, cortisol, testosterone and catecholamines and gives an insight of acute and chronic effects of aerobic, anaerobic, resistance and endurance exercises on these hormones.